2017
DOI: 10.1002/acr.23111
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab for Long‐Term Treatment of Psoriatic Arthritis: A Two‐Year Followup From a Phase III, Randomized, Double‐Blind Placebo‐Controlled Study

Abstract: Secukinumab provided sustained improvements in PsA at 2 years, with very little radiographic progression. Treatment was well tolerated over the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 27 publications
(46 reference statements)
11
74
0
4
Order By: Relevance
“…In agreement with previous studies (3,8,9,11,(13)(14)(15)(16), secukinumab treatment in FUTURE 1 was shown to be efficacious in both anti-TNF-naïve and anti-TNF-IR patients, with clinical responses generally higher in anti-TNF-naïve patients than in anti-TNF-IR patients. Improvement in ACR and PASI responses was achieved in patients who escalated from secukinumab 150 to 300 mg, indicating a benefit of dose escalation in patients who require additional control of symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In agreement with previous studies (3,8,9,11,(13)(14)(15)(16), secukinumab treatment in FUTURE 1 was shown to be efficacious in both anti-TNF-naïve and anti-TNF-IR patients, with clinical responses generally higher in anti-TNF-naïve patients than in anti-TNF-IR patients. Improvement in ACR and PASI responses was achieved in patients who escalated from secukinumab 150 to 300 mg, indicating a benefit of dose escalation in patients who require additional control of symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…The safety profile of secukinumab was consistent with that previously reported for PsA (3,9,(12)(13)(14)(15)(16)(17) and psoriasis (6). No new or unexpected safety signals were observed in patients with PsA over a treatment period of up to 5 years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[29][30][31] These anti-IL-17A biologics have been shown effective in psoriasis as demonstrated by their high PASI 75 response rates (71-83% at 12 weeks). [29][30][31] Anti-IL-17A biologics have also been shown to improve symptoms of psoriatic arthritis, 32,33 ankylosing spondylitis 34 and rheumatoid arthritis. 35 In Phase II studies of patients with IBD, blocking IL-17A was ineffective.…”
Section: Introductionmentioning
confidence: 99%